Main dalam Perspektif Vygotsky pada Anak Pra-Sekolah - lsmail, Khaidzir Hj; Rizfyanti, Charyna Ayu (ANIMA Indonesian Psychological Journal, 2002)
Vygotsky owns a notion of what play is to preschoolers. Play is not just an aimless activity for young children. It is a median to learn to solve a problem. Problem solving skills can be taught through indulging in a task which is very difficult if not impossible to solve by the child alone. He introduces a concept called scaffolding which allows potential cognitive development to take place in the Zone of Proximal Development (ZPD). ScaffoIding is aimed at guiding the child to solve problem using strategies created in the social interaction with the help of a more knowledgeable or capable person.